Correction: Developing a Raman spectroscopy-based tool to stratify patient response to pre-operative radiotherapy in rectal cancer. Issue 13 (16th June 2021) - Kirkby, Chloe J.; Gala de Pablo, Julia; Tinkler-Hundal, Emma; Wood, Henry M.; Evans, Stephen D.; West, Nicholas P.
Abstract : Correction for 'Developing a Raman spectroscopy-based tool to stratify patient response to pre-operative radiotherapy in rectal cancer' by Chloe J. Kirkby et al., Analyst, 2021, 146, 581–589, DOI: ; 10.1039/D0AN01803A .